Severe Hypercalcaemia as a Consequence of Parathyroid Crisis - A Case Report - R, Hasan; MR, Alam; F, Jahan; AKMS, Rahman; MS, Islam (Archives of Clinical and Medical Case Reports, 2021)
36-years old man presenting with the complaint of sudden severe upper abdominal pain, vomiting and polyuria with raised serum creatinine (2.74 mg/dl), serum calcium (19.68 mg/dl) and intact parathyroid hormone (iPTH) (2014.70 pg/ml) level. His ultrasound image of neck region demonstrated hypoechoic mass (12×10 mm) at left inferior parathyroid gland. Parathyroid schintography reported positive for parathyroid adenoma (left lower). He underwent medical management followed by parathyroidectomy. Optimum serum calcium concentration is essential for homeostasis and function of multiple organ systems. Severe hypercalcaemia is rare but life threatening complication of primary hyperparathyroidism (PHPT). In order to prevent mortality, it is necessary to provide immediate appropriate treatment by correcting hypercalcaemia and dehydration.